GnRH and neuropeptide regulation of gonadotropin secretion from cultured human pituitary cells - Wormald, Patricia J (Division of Chemical Pathology, 2018)
Gonadotropin-releasing hormone (GnRH) and its superactive analogues are currently being used in the treatment of a number of endocrine disorders, such as endometriosis, precocious puberty, infertility and prostatic cancer. Selection of these analogues for clinical use have been previously based on their activities in animal models. This thesis has therefore investigated the binding characteristics of the human GnRH receptor, in comparison to those of the rat receptor, as well as the activities of a number of GnRH analogues for stimulating luteinising hormone (LH) and follicle stimulating hormone (FSH) secretion from cultured human pituitary cells. The establishment of a human pituitary bioassay system has further made possible the investigation of the direct regulatory roles of GnRH and other neuropeptides in man. To date, such studies in man have been performed in vivo and are thus complicated by the simultaneous interactions of numerous modulators.